AUDIT FIRM SIZE AND THE LEVEL OF EARNINGS MANAGEMENT IN THE INDUSTRIAL GOODS SECTOR IN NIGERIA - Jack, Mpakaboari Mathew; Micah Leyira Christain (Scholar Express Journals, 2021)
The study examined whether there is a significant relationship between audit firm size and the level of earnings management in the industrial goods sector in Nigeria. In this study, audit firm size is the dimension of the independent variable. The level of earnings management is measured by using a discretionary accruals estimation method: the Modified Jones model and Asset turnover margin diagnostics. The effect of audit firm size on earnings management is expected to be negative, as a qualitatively good audit is expected to constrain earnings management. This effect was examined by employing a multiple regression model using a sample of 14 firms in the industrial goods sector listed on Nigeria stock exchange (NSE) from 2009 - 2019. The results suggest that industrial goods sector in Nigeria context shows that the level of earnings management is not directly affected by audit firm size. This could imply that audit firms should improve their performance and that regulatory agencies should improve their supervision in order to enhance audit quality and restrain earnings management. Although prior (international) research predominantly does show significance, the absence of significance in this study could be explained by the relatively small sample size or the context in which the study takes place. It is recommended giant audit firms should intensify effort in supervising the preparation of accounting statements in the firms to enforce obedience to standards (IFRS and various ISAs)
Keywords: Audit; NSE; Industrial Goods Sector